Cell painting with an engineered EPCR to augment the protein C system - Bouwens, Eveline A. M.; Stavenuiter, Fabian; Mosnier, Laurent O. (Thrombosis and Haemostasis, 2015)
The protein C (PC) system conveys beneficial anticoagulant and cytoprotective effects in numerous in vivo disease models. The endothelial protein C receptor (EPCR) plays a central role in these pathways as cofactor for PC activation and by enhancing activated protein C (APC)-mediated protease-activated receptor (PAR) activation. During inflammatory disease, expression of EPCR on cell membranes is often diminished thereby limiting PC activation and APC’s effects on cells. Here a caveolae-targeting glycosylphosphatidylinositol (GPI)-anchored EPCR (EPCR-GPI) was engineered to restore EPCR’s bioavailability via “cell painting.” The painting efficiency of EPCR-GPI on EPCR-depleted endothelial cells was time- and dose-dependent. The EPCR-GPI bioavailability after painting was long lasting since EPCR surface levels reached 400 % of wild-type cells after 2 hours and remained > 200 % for 24 hours. EPCR-GPI painting conveyed APC binding to EPCR-depleted endothelial cells where EPCR was lost due to shedding or shRNA. EPCR painting normalised PC activation on EPCR-depleted cells indicating that EPCR-GPI is functional active on painted cells. Caveolin-1 lipid rafts were enriched in EPCR after painting due to the GPI-anchor targeting caveolae. Accordingly, EPCR painting supported PAR1 and PAR3 cleavage by APC and augmented PAR1-dependent Akt phosphorylation by APC. Thus, EPCR-GPI painting achieved physiological relevant surface levels on endothelial cells, restored APC binding to EPCR-depleted cells, supported PC activation, and enhanced APC-mediated PAR cleavage and cytoprotective signalling. Therefore, EPCRGPI provides a novel tool to restore the bioavailability and functionality of EPCR on EPCR- depleted and -deficient cells.
Keywords: Endothelial protein C receptor; glycosylphosphatidylinositol anchors; protease-activated receptors; protein C; vascular endothelium